The Yuan goes global - Singapore Management University (Institutional Knowledge at Singapore Management University, 2017)
Professor Chow Hwee Kwan studies how Asian countries manage their currencies, and the impact of these policies on their economies. See the paper: Is the Renminbi East Asia’s dominant reference currency? A reconsideration